The Role Of Economics and Enterpreneurship Education On Students' Financial Behavior: A Systematic Literature Review - Nuryamin Budi; Vina Mustika Sidiq; Muhammad Ilyas Hamzah; Wa Ode Sitti Liliyani; Syarifah Ni’mah; Intan Nadya Shafwah (Journal of Economic Education and Entrepreneurship Studies, 2026)
This study aims to synthesize recent empirical evidence on the role of economics, entrepreneurship, and financial education in shaping students’ financial behavior, with particular attention to psychological mechanisms and behavioral biases. A systematic literature review was conducted using the PRISMA 2020 framework. Scopus-indexed empirical articles published between 2020 and 2025 were identified and screened according to explicit eligibility criteria. The synthesis focused on educational interventions, financial literacy, financial behavior, self-control, financial self-efficacy, overconfidence, and herding behavior. The review indicates that educational interventions can improve financial knowledge, but behavioral change is not always automatic. Financial behavior is more consistently strengthened when financial literacy is supported by self-control, self-efficacy, locus of control, and awareness of cognitive biases. Contextual factors such as gender, family background, peer influence, and digital environments also shape the effectiveness of education. The review is limited by its reliance on Scopus, the heterogeneity of included studies, and the dominance of cross-sectional designs. This study contributes by integrating economics and entrepreneurship education with behavioral finance mechanisms to explain the knowledge-action gap in students’ financial behavior.